The effect of intraperitoneal and intramammary immunization of sheep on the numbers of antibody-containing cells in the mammary gland, and antibody titres in blood serum and mammary secretions. - Sheldrake, R F (1985)
The contribution of gut-associated lymphoid tissue (GALT) to the local response in the mammary gland is well documented in laboratory animals and has been evaluated in this study in ruminants. Ewes were immunized intraperitoneally (IP) with antigen in Freund's complete adjuvant (FCA), a procedure which stimulates the production of antibodies of the IgA class in the intestine, and challenged intramammarily (IMam) either during colostrum formation or mammary gland involution. Despite a substantial IgA antibody-containing cell (ACC) response in the intestine in IP immunized sheep, there was no evidence to suggest a relocation of IgA-specific ACC to the mammary gland. There was, however, an IgA antibody response in mammary secretion of IP immunized animals, regardless of whether the mammary gland was locally immunized, but the origin of this antibody is unclear. IP/IMam immunized sheep did have an enhanced antigen-specific ACC response of the IgG1 isotype in locally immunized glands, but whether these cells were of GALT or systemic origin is also unclear.